Choleretic effects of acetophenone derivatives and analogues on rats - CHAN Y S; CHIANG T C; CHENG Y Y; CHOANG TAI K F; CHANG H M (Acta Pharmacologica Sinica, 2016)
Fifteen acetophenone derivatives promoted the bile secretion in normal rats. Among these compounds, chlorophenyl methyl ketone and hydroxyl-acetophenones exhibited stronger choloretic effect. Orthochloroacetophenone (No 8) had even a greater choleretic power than the well-known choleretic agent sodium dehydrocholate (No 5). Increase in bile flow was not merrely a dilution effect, as the total solids excreted through the bile were also increased while the concentration of solids in the bile was significantly lowered. Bile flow in rats with moderate choleresis induced by acute ANIT (25 mg/kg, ig) intoxication was improved by ortho-chloro-(No 8) and 2,4-dichloro-acetophenones (No 11).